Hybrid Philanthropy for SDGs: A Comparative Analysis of Funding Distribution Challenges in Remote Areas of Singapore and India - Mohamad Syahreza Pahlevi; Rozi Andrini (MD Research Center Yogyakarta, 2025)
This research examines the distribution of philanthropic funds in the context of achieving the Sustainable Development Goals (SDGs) in remote areas, focusing on two countries: Singapore and India. The approach used is a qualitative literature study aimed at exploring the challenges and opportunities in the distribution of philanthropic funds and understanding the factors influencing the success or failure of philanthropic initiatives in achieving development goals. The main findings indicate that despite significant philanthropic funding efforts in both countries, there is a substantial gap between the initiatives’ objectives and local needs. In India, misalignment between philanthropic policies and socioeconomic conditions, along with infrastructure limitations, often hinders program effectiveness. Meanwhile, in Singapore, although government policy support and digital technology can accelerate resource mobilization, difficulties remain in reaching underrepresented remote areas. The study also highlights the importance of cross-sector collaboration and transparency in fund distribution processes to ensure greater impact on SDG achievement. The scientific contribution of this study introduces the concept of hybrid philanthropy as a potential new model for managing funds for sustainable development purposes. Furthermore, it underscores the need for further research on the roles of government and social institutions in creating a more inclusive and adaptive philanthropic ecosystem responsive to local conditions.